Overview of Consumptive Behavior in High School Students: Gambaran Perilaku Konsumtif pada Siswa Sekolah Menengah Atas - Mochammad Rifqi; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the number of Consumptive Behaviors of SMK YAPALIS Krian students. This study aims to determine the description of consumptive behavior in students of SMK YAPALIS Krian. The variable in this study is Consumptive Behavior. The sample in this study were students of SMK YAPALIS Krian, totaling 286 students of grade 10 to grade 12. Determination of the sample using proportionate stratified random sampling on students of SMK YAPALIS Krian. Data collection was carried out using a Consumptive Behavior psychology scale with a Likert scale model. The analysis technique used descriptive quantitative with the help of SPSS 18.0 for windows. The results of the analysis of Consumptive Behavior in YAPALIS Krian Vocational High School students obtained the results of 21 students who had very high Consumptive Behavior, 63 students had high Consumptive Behavior, 116 students had moderate Consumptive Behavior, 67 students who have Low Consumptive Behavior and 19 students have Low Consumptive Behavior, it can be said that YAPALIS Krian Vocational School students have Consumptive Behavior with a Medium Category tending to the top Highlights: Consumptive behavior prevalence: The study highlights the distribution of consumptive behavior among students of SMK YAPALIS Krian, indicating the varying levels of consumption exhibited by the students. Sample size and methodology: The study involved a sample of 286 students from grades 10 to 12, selected through proportionate stratified random sampling, providing a comprehensive representation of the student population. Descriptive analysis results: The analysis revealed that a significant portion of the students exhibited moderate to high levels of consumptive behavior, emphasizing the need for further investigation and potential intervention to address this behavior pattern. Keywords: Consumptive Behavior, SMK YAPALIS Krian, Students, Description, Analysis